Improvement of Fractional Flow Reserve after Percutaneous Coronary Intervention Does Not Necessarily Indicate Increased Coronary Flow - Rikuta Hamaya; Yoshihisa Kanaji; Eisuke Usui; Masahiro Hoshino; Tadashi Murai; Taishi Yonetsu; Tsunekazu Kakuta (European Cardiology Review)
Coronary flow is expected to increase by epicardial lesion modification after successful percutaneous coronary intervention (PCI) in stable angina. According to the concept of fractional flow reserve (FFR), the improvement in FFR after PCI reflects the extent of coronary flow increase. However, this theory assumes that hyperaemic microvascular resistance does not change after PCI, which is being refuted in recent studies. The authors quantitated regional absolute coronary blood flow (ABF) before and after PCI using a thermodilution method and compared it with FFR in 28 patients with stable coronary artery disease who had undergone successful PCI. Although FFR indicated changes in ABF, with a mean difference of −5.5 ml/min, there was no significant relationship between individual changes in FFR and in ABF (R=0.27, p=0.16). The discrepancy was partly explained by changes in microvascular resistance following PCI. These results suggest that changes in FFR do not necessarily indicate an increase in absolute coronary blood flow following PCI in individual patients, although they could be correlated in a cohort level.